STRATEGI PENGELOLAAN SAMPAH DI KAWASAN KEPULAUAN SERIBU - Sahwan, Firman Laili (Jurnal Teknologi Lingkungan, 2004)
The district of Kepulauan Seribu consists of 110 islands which cover 6.997 km2 area in Teluk Jakarta. The local government relises that for supporting their sustainable development need a good environmental management such as solid waste management and treatment. The clean beach and settlement are very important for developing tourism and mariculture. Kepulauan Seribu has to set up the profesional integrated solid waste management that carried out by all the stakeholders. The clean island is investment for Kepulauan Seribu for attracting investor, economic actor and tourists.